Effect of processing parameters on the microstructure and properties of an Nb microalloyed steel - Bakkaloglu, A (ELSEVIER SCIENCE BV, 2002)
High strength low alloy (HSLA) steels have demonstrated superior mechanical properties through controlled rolling (CR). In the present investigation, the effects of processing parameters, such as finish rolling temperature, rolling reduction, inter-pass time and cooling rate, on the final microstructure and mechanical properties of a grade X52 type HSLA steel has been studied by tensile and charpy impact tests and optical microscopy and scanning electron microscopy. To yield better mechanical properties of X52 microalloyed steel grade, the optimization of the rolling process in the laboratory experiment and rolling mill has been carried out. It has been found that the tensile and impact properties of X52 steel are significantly improved by controlled rolling in the (alpha+gamma) two-phase region. The cause of such improvement in mechanical properties of the control-rolled steel is correlated with changes in microstructure, i.e. ferrite grain refinement, a large number of subgrains and high dislocation density. Furthermore, the low carbon contents exhibited by these steels cause evident improvement in their toughness and weldability. Finally, a controlled rolling process in the (alpha+gamma) two-phase region of X52 steel plates has been suggested. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: controlled rolling; controlled cooling; processing parameters; microalloying; HSLA steel; mechanical properties; (alpha plus gamma) phase region; MECHANICAL-PROPERTIES; CARBON; Materials Science; Physics